Kombinasi overdenture dan teleskop dengan kondisi lingir knife edge - Suryanto Purba; Syafrinani . (Makassar Dental Journal PDGI Makassar, 2018)
The anatomical condition of the oral cavity and remaining teeth of the patient influence the design planning of a denture. Lower jaw with knife edge ridge is less desirable for retention and stabilization of denture. The remaining teeth can’t be used for retention, stabilization and maintaining the density of the jaw bone. Thus, the remaining teeth do not require extraction although the teeth may not be used as retention for conventional dentures. The purpose of this case study is to explain manufacture of overdenture and telescopic denture combination with utilize the remaining teeth. It was reported a 47 year-old woman came to RSGMP the Faculty of Dentistry USU with the complain that she wishes to replace the upper jaw denture and lower jaw denture that was made a year ago because it is loose and the patient feels pain whenever she chews. Before this, the patient has worn a denture and has the same complain and she doesn’t use it anymore. On the upper jaw, flabby tissue could be seen in the anterior region. On the lower jaw, the ridge is shaped like a knife edge and the remaining teeth are 41, 31, 32, 33 with mobility of 2 and extrusion of 2 mm. In this case, for the lower jaw overdenture and telescopic denture combination was made. It utilizes the remaining teeth as abutments for additional retention and stabilization. It was concluded that overdenture and telescopic denture combination and the utilization of remaining teeth can increase the retention and stabilization which contributes to the treatment success of the denture.